Response of Vibration Reduction with Additional of Dual Dynamic Vibration to The Main System - Talifatim Machfuroh; Zakiyah Amalia; Fica Aida Nadhifatul Aini (PT. ELSHAD TECHNOLOGY INDONESIA, 2023)
Excessive vibration in a system occurs when the force acting on a system is close to the natural frequency of the system. This vibration can be reduced by adding a dynamic vibration absorber (DVA) to the system. Several researchers have done a lot of research related to DVA and dual DVA (DDVA) placement in the main system. In this research, we conducted a study of the effect of DDVA-dependent addition on translational and rotational vibration responses in the 2-dof main system. This research was started by building a prototype of a 2 DOF vibration system without DDVA and with DDVA. From the prototype, equations of motion and block simulations were then made to determine changes in vibration characteristics that occur in the main system. From the research results it was found that the placement of the DDVA-dependent cantilever absorber at the end of the system with rI 1/10 was able to reduce the vibration of the main system with a percentage reduction at a frequency of 12.78 Hz of 94.1681% for the translation direction and 15.3878% for the rotation direction. Changes in the distance ratio and the inertia ratio of the absorber mass do not affect the DDVA-dependent ability to reduce vibrations in the translation direction.